Ethiopian Poverty Reduction and Transport Strategy Review - World Bank (Addis Ababa, 2014)
The strategic objective of Sub-Saharan Africa Transport Policy Program (SSATP) long term development plan is to anchor transport policies and strategies in national strategies for poverty reduction, so as to enable the transport sector contribute fully to pro-poor growth and poverty reduction. To this end, many SSA countries have conducted the Poverty Reduction and Transport Strategy Review (PRTSR) workshops to assess and review the coherence and link between their poverty reduction strategies and transport strategies and policies. This report presents the processes and the outcomes of the three workshops held between July and September 2007 that reviewed Ethiopia's road sector policy/programs and PASDEP. The first workshop was conducted from 26 - 28th July 2007. In this workshop, stakeholders extracted relevant information from the A Plan for Accelerated and Sustained Development to End Poverty (PASDEP) regarding goals, objectives and targets as well as the difficulties on access and mobility. They also identified the interventions concerning transport infrastructure and services in the priority economic and social sectors, population groups, and cross-cutting issues. They also reviewed the PASDEP and its treatment of transport related issues; the second workshop was conducted from 17 - 19th August 2007. During this workshop, participants were able to identify the strengths and weaknesses of Ethiopia's road policy/ programs in terms of its contribution to poverty reduction. They also gave suggestions on how the road sector policy/programs might be improved to better contribute to poverty reduction; and the third workshop was conducted from 14 - 16th September 2007. In this workshop stakeholders assessed the current institutional arrangements and mechanisms for policy dialogue and formulations of both PASDEP and the road sector policy/programs. Based on the findings of the workshops, the stakeholders also designed an action plan that can influence the adoption of policies and strategies that links transport/road sector with poverty reduction.